Application of the Wave Based Technique for steady-state semi-infinite sound radiation analysis - Rejlek, Jan; Hepberger, Achim; Priebsch, Hans-Herwig; Pluymers, Bert; Desmet, Wim (Computer Assisted Methods in Engineering and Science, 2022)
This paper reports on the development of a novel wave based prediction technique for the steady-state sound radiation analysis of three-dimensional semi-infinite problems. Instead of simple polynomial shape functions, this method adopts an indirect Trefftz approach, in which it uses the exact solutions of the governing differential equation for the field variables approximation. Since a fine discretization is no longer required, the resulting wave based models are substantially smaller than the element-based counterparts. Application of the proposed approach to various validation examples illustrates an enhanced computational efficiency as compared with element-based methods.